ANALISIS PENGARUH BOBOT AWAL DOC TERHADAP PRODUKTIVITAS AYAM PEDAGING POLA KEMITRAAN - Tito Hermawan; Rico Anggriawan; Camal Adi Maschur; Diyah Ayu Chandra (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2025)
As time goes by and the soaring population of Indonesia and the image that Indonesia is facing a demographic bonus, namely the phenomenon when the number of people of productive age (15 - 64 years) is greater than the number of people of non-productive age (65 years and over) is a rare moment that only happens once in the history of a nation.This phenomenon can be a great opportunity in the development of the country towards the Golden Indonesia 2045 if accompanied by the quality of good human resources, of course this is not spared from the availability of nutritious food sources of animal protein, one of which can be an option, namely chicken meat. Therefore, farmers are required to always increase their productivity, one of the things that affects productivity is the initial weight of the doc. The purpose of this study was to determine the relationship between the initial weight of the doc and the productivity of broilers in partnership patterns that are useful to help readers and farmers in choosing a partnership company that can provide maximum profit. Materials and research methods using by direct survey with 2 farmers who have the same age, type of doc, type of feed and partnership company but have different doc weights, namely farmer 1 with super seed doc while farmer 2 with young seed doc. The results of our research clearly show that the initial weight of the super doc, which is 37 - 41 grams, produces a harvest weight according to the broiler performance target and suppresses the FCR rate so that the farmer's income is greater than the young seed doc with an initial weight below 37 grams, but has no significant effect on the mortality rate that we studied and recorded body weight every week until the chicken is harvested, so the conclusion is that there is a real relationship between the initial weight of the doc and the productivity of the broiler partnership pattern.